Adaptação transcultural e avaliação das propriedades de medida do instrumento Start Back Clinical Measurement Tool - Avanzi, Marina Athayde (2019)
Introduction: Low back pain is a very common symptom experienced by people of all ages and is considered as a public health problem. Clinical practice guidelines have been recommending the use of a biopsychosocial model for better evaluation and treatment of the patient. Therefore, the instrument STarT Back Screening Tool (SBST) was created to identify patients’ prognostic factors and to improve clinical prognostic. However, the instrument was not designed to monitor change in patients’ clinical condition thus, Keele University developed an instrument called STarT Back Clinical Measurement Tool (SBCMT), which is focused in monitoring patients clinical change. However, the SBCMT has not yet been adapted to Portuguese, and to this date, the measurement properties of this instrument have not yet been tested even in its English version. Objective: cross-cultural adaptation of the SBCMT to Portuguese and evaluate its measurement properties on reliability (internal consistency, reliability, measurement error), construct validity (hypotheses-testing), responsiveness, besides the characteristics of interpretability, (ceiling and floor effect, and generalization). Methods: The study was divided in two stages. In the first stage we translated the SBCMT to Brazilian Portuguese following the translation and cross-cultural adaptation guidelines for self-assessment tools. Then, a pre-test was performed, with the purpose of verifying the interpretability of the instrument. The pre-test was applied to two different groups; the first consisted of 20 physiotherapists, whilst the second was formed by 30 patients with low back pain. In the second stage of the study we tested the measurement properties of the SBCMT instrument in 103 patients with nonspecific low back pain who sought physiotherapeutic care. The patients were evaluated in three different moments: 1) at baseline; 2) after 24/48 hours; 3) 6 weeks after baseline. Statistical analysis: The internal consistency was calculated using Alpha Cronbach, reliability was calculated using the Intraclass Correlation Coefficient (ICC) of type 2.1, and their respective 95% confidence intervals (CI).The agreement was analyzed by Standard Measurement Error (EPM) and the ceiling and floor effect was calculated by the maximum and minimum scoring frequency by SBCMT. The construct validity was evaluated by the hypothesis tests by Kappa and Pearson correlation, and responsiveness was assessed by Pearson correlation, Receiver Operating Characteristics Curve (ROC), and Effect size. Construct validity and responsiveness are considered positive when at least 75% of the results correspond to the hypotheses. Results: The interpretability of the instrument reached consensus, we did not find differences of content and meaning. In the pre-test of the adapted instrument, nine patients presented difficulty in answering item five, this item was reformulated, and we verified a better understanding of the patients. The internal consistency of the SBCMT total score presented an adequate result of Cronbach's Alpha 0.78, with 0.71 being the smallest item and 0.79 the largest item deleted. The reliability for each item and for the total score was considered as moderate to substantial ranging from 0.42 to 0.80 (95% CI). The agreement of the SBCMT for each item was considered as doubtful and negative (ranging from 14.71% to 24.42%) and for the total score was considered as doubtful (11,45). The validity of the construct and the responsiveness were considered positive, with 75% of the results corresponding to the hypotheses elaborated a priori. Conclusion: The process of cross-cultural adaptation of the STarT Back Clinical Measurement Tool (SBCMT) to Brazilian-Portuguese was performed in an acceptable manner. The SBCMT-Brazil presented adequate results for internal consistency, the construct validity was considered positive, and SBCMT was responsive to measure clinical change. The SBCMT-Brazil instrument was unstable regarding reliability and a concordance when evaluated by the item of the instrument in which the objective is superior to the EPM. We recommend that other studies check the measurement property, so we indicate the use of the START Back Clinical Measurement Tool only for total score.